Frontiers in Algorithmics and Algorithmic Aspects in Information and Management Joint International Conference, FAW-AAIM 2012, Beijing, China, May 14-16, 2012. Proceedings - Snoeyink, Jack.; Lu, Pinyan; Su, Kaile; Wang, Lusheng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 6th International Frontiers of Algorithmics Workshop, FAW 2012, and the 8th International Conference on Algorithmic Aspects in Information and Management, AAIM 2012, jointly held in Beijing, China, in May 2012. The 33 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 81 submissions. The papers are organized in topical sections on algorithms and data structures, algorithmic game theory and incentive analysis, biomedical imaging algorithms, communication networks and optimization, computational learning theory, knowledge discovery, and data mining, experimental algorithmic methodologies, optimization algorithms in economic and operations research, pattern recognition algorithms and trustworthy algorithms and trustworthy software.
Keywords: Computer science; Data structures (Computer science).; Information theory; Computer software; Computational complexity; Information Systems; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Mathematics of Computing; Theory of Computation; Management of Computing and Information Systems; Data Structures